Analysis of gaps and possible interventions for improving water productivity in crop livestock systems of Ethiopia - Descheemaeker, Katrien K.; Amede, Tilahun; Haileslassie, Amare; Bossio, Deborah A. (Cambridge University Press, 2011)
Low crop and livestock productivities in the mixed farming systems of Ethiopia hamper efforts to meet the increasing food demands from a stressed natural resource base. Important reasons for the low agricultural productivity are water scarcity and poor spatial and temporal rainfall distribution. Although improving agricultural water productivity would safeguard people’s livelihoods and the environment, the lack of information on best bet interventions and strategies to achieve this impedes targeted decision making. Therefore, the aim of this study was to conduct an ex-ante evaluation of the potential effect of selected interventions on livestock water productivity (LWP) in mixed crop-livestock systems. Baseline data were collected from a water scarce area in the Ethiopian highlands. An analysis of productivity gaps and stakeholder interviews helped to identify promising interventions, which were categorized in three groups related to feed, water and animal management. A spreadsheet model was developed that was composed of the various production components of the farming system, their interactions and influencing factors. By linking water use for feed production with livestock products through the energy supplied by the feeds, the potential effect of interventions on LWP could be simulated. The evaluation showed that the various interventions targeting feed, water and animal management could result in LWP improvements ranging from 4 to 94%. Feed and energy water productivity increased particularly with interventions like fertilizer application, and the introduction of fodder trees, concentrates, improved food-feed crops, and soil and water conservation measures. Combining the different interventions led to a stronger improvement than any of the single interventions. The results of the evaluation can inform policy-makers and development actors on which best bets to promote and invest in.